Establishment and Distribution of Laricobius spp. (Coleoptera: Derodontidae), a Predator of Hemlock Woolly Adelgid, Within the Urban Environment in Two Localities in Southwest Virginia. (30th September 2019) - Foley, Jeremiah R; McAvoy, Thomas J; Dorman, Seth; Bekelja, Kyle; Kring, Timothy J; Salom, Scott M
Abstract: Hemlock woolly adelgid (HWA), Adelges tsugae Annand, is a highly destructive non-native pest lethal to eastern hemlock, Tsuga canadensis (L.) Carrière, and Carolina hemlock, T. caroliniana Engelmann. Fifty years following the first observation of HWA in eastern North America, a predatory beetle, Laricobius nigrinus Fender, was evaluated, approved, and released as a biological control agent. Efforts were made to mass rear L. nigrinu s with the goal of redistributing the beetles on public lands, typically in forest ecosystems, as a secondary option to silvicultural and chemical controls. The majority of L. nigrinus releases has occurred on public lands. Herein, we report the observation of L. nigrinus within the urban environment outside of known release locations. Two towns, Blacksburg and Radford, were divided into 0.40 km 2 grids. A total of 27 and 19 grids were randomly selected from each town, respectively. Hemlocks were present in 44 and 42% of the grids surveyed in Blacksburg and Radford, respectively. In Blacksburg and Radford, 86 and 100% of the grids with hemlocks were infested with HWA, and of those infested hemlocks, Laricobius spp. was present in 100 and 75% of grids, respectively. A total of 154 Laricobius spp. (98% L. nigrinus and 2% Laricobius rubidus ) adults were collected between each town. While it is unclear the level of control L. nigrinus has on reducing HWA's impact, the establishment of this biological control agent in the urban environment is an additional level of predation, that would otherwise not be present, for homeowners with HWA-infested trees.